Clinical predictors for oropharyngeal dysphagia and laryngeal dysfunction after lung and heart transplantation. Issue 6 (30th July 2019) - Black, Rebecca J.; Bogaardt, Hans; McCabe, Patricia; Glanville, Allan R.; MacDonald, Peter; Madill, Catherine
Abstract: Background: Oropharyngeal dysphagia and laryngeal dysfunction are two lesser known complications after lung and heart transplantation. The presence of these features places this immunocompromised population at high risk of pulmonary complications and subsequent medical deterioration. Early identification of swallowing and voice dysfunction would be beneficial to optimize management. Aims: To examine the association between patient risk factors and postoperative outcomes with referral to speech pathology (SP) following signs of swallowing and voice dysfunction. Methods & Procedures: A retrospective review was conducted on demographic data, patient risk factors and postoperative course in 284 patients following lung and/or heart transplantation between 2010 and 2013. Variables were analysed for any association between pre‐ and postoperative factors and SP referral. Outcomes & Results: A total of 24% were referred to SP with a mean age of 47 years. Binary logistic regression identified a statistically significant association between the number of intubations (odds ratio (OR) = 2.066, p = 0.028), intubation duration (OR = 1.004, p < 0.01), length of stay in the intensive care unit (ICU) (OR = 1.068, p < 0.01), and number of ICU admissions (OR = 1.384, p = 0.046) and SP referral. Intubation time and the total days in ICU were greater for patients referred to SP. Mortality also increased for these variables and for the numbers of reintubations and readmissions. Analysis of pre‐operative risk factors revealed cerebrovascular disease to be a significant predictor of SP referral (OR = 6.747, p = 0.032). Conclusions & Implications: This study demonstrates significant clinical indicators for referral to SP for the management of oropharyngeal dysphagia and laryngeal dysfunction in patients after lung or heart transplantation. Further studies are needed to investigate the most efficacious intervention approaches to manage swallowing and voice dysfunction in these patients.